1956
DOI: 10.1136/adc.31.157.189
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic Separation of Reducing Sugars in the Urines of Newborn Babies

Abstract: The application of paper chromatography to the qualitative analysis of reducing sugars by Partridge (1946) has greatly simplified the detection of these substances in biological fluids. In particular it has provided an accurate and comparatively easy method of separating reducing sugars in the urine. This has proved of great value in the investigation of such a condition as congenital galactosaemia, about which disease there has been much recent interest (Bray, Isaac and Watkins, 1952;Hudson, Ireland, Ockende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1959
1959
1990
1990

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Bickel (1961), studying 155 specimens of urine from 88 normal neonates, found the mean 'normal' lactose to be between 20 mg/100 ml and 50 mg/100 ml between the third and seventh day of life. Haworth and McCredie (1956) found that about half of 50 normal breast-fed babies had reducing sugars in their urine at some time during the first weeks of life and a substantial minority had more than 50 mg/100 ml, yet more than 15 mg/100 ml of sugar in the urine of neonates who have had surgery has been regarded by some workers as confirming a diagnosis of sugar intolerance (Howat and Aaronson, 1971).Thus, though clinical diagnosis of sugar malabsorption in the newborn is usually based on finding an excess of reducing susbstances in a watery stool, what constitutes an excess is at present uncertain. In view of this we undertook a study of stool and Received 23 October 1975. urine sugar levels in normal breast-and bottle-fed newborn infants.…”
mentioning
confidence: 99%
“…Bickel (1961), studying 155 specimens of urine from 88 normal neonates, found the mean 'normal' lactose to be between 20 mg/100 ml and 50 mg/100 ml between the third and seventh day of life. Haworth and McCredie (1956) found that about half of 50 normal breast-fed babies had reducing sugars in their urine at some time during the first weeks of life and a substantial minority had more than 50 mg/100 ml, yet more than 15 mg/100 ml of sugar in the urine of neonates who have had surgery has been regarded by some workers as confirming a diagnosis of sugar intolerance (Howat and Aaronson, 1971).Thus, though clinical diagnosis of sugar malabsorption in the newborn is usually based on finding an excess of reducing susbstances in a watery stool, what constitutes an excess is at present uncertain. In view of this we undertook a study of stool and Received 23 October 1975. urine sugar levels in normal breast-and bottle-fed newborn infants.…”
mentioning
confidence: 99%
“…It has previously been shown that reducing sugars are frequently excreted in the urine by mature and premature newborn babies (Haworth and McCredie, 1956;Haworth and MacDonald, 1957). Other workers, using paper chromatographic methods, have also found small amounts of sugars in the urines of children and usually higher concentrations of lactose and galactose in urines from young babies (Woolf, 1951;Apthorp, 1957;Bickel, 1959).…”
mentioning
confidence: 99%
“…As noted earlier, other investigators have identified lactose in the urine of subjects receiving lactose and suggested a higher ex cretion of this disaccharide in early infancy compared to later in life [2][3][4][5][6][7][8]. The studies by Haworth and McCredie [2], Woolf and Norman [3], and Haworth [4] demonstrated qualitatively that urine contained lactose fol lowing the ingestion of the disaccharide.…”
Section: Discussionmentioning
confidence: 80%
“…The studies by Haworth and McCredie [2], Woolf and Norman [3], and Haworth [4] demonstrated qualitatively that urine contained lactose fol lowing the ingestion of the disaccharide. However, there was no controlled quantita tive assessment of lactose excretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation